Aucubin Promotes Osteogenic Differentiation and Facilitates Bone Formation through the lncRNA-H19 Driven Wnt/β-Catenin Signaling Regulatory Axis - Yong-xin Mai; Zhi-peng Li; Feng-xiang Pang; Shu-ting Zhou; Nan Li; Yu-yan Wang; Jin-fang Zhang (Stem Cells International)
Objectives. Traditional Chinese medicine Cortex Eucommiae has been used to treat bone fracture for hundreds of years, which exerts a significant improvement in fracture healing. Aucubin, a derivative isolated from Cortex Eucommiae, has been demonstrated to possess anti-inflammatory, immunoregulatory, and antioxidative potential. In the present study, our aim was to explore its function in bone regeneration and elucidate the underlying mechanism. Materials and Methods. The effects of Aucubin on osteoblast and osteoclast were examined in mouse bone marrow-derived mesenchymal stem cells (BM-MSCs) and RAW 264.7 cells, respectively. Moreover, the lncRNA H19 and Wnt/β-catenin signaling were detected by qPCR examination, western blotting, and luciferase activity assays. Using the femur fracture mice model, the in vivo effect of Aucubin on bone formation was monitored by X-ray, micro-CT, histomorphometry, and immunohistochemistry staining. Results. In the present study, Aucubin was found to significantly promote osteogenic differentiation in vitro and stimulated bone formation in vivo. Regarding to the underlying mechanism, H19 was found to be obviously upregulated by Aucubin in MSCs and thus induced the activation of Wnt/β-catenin signaling. Moreover, H19 knockdown partially reversed the Aucubin-induced osteogenic differentiation and successfully suppressed the activation of Wnt/β-catenin signaling. We therefore suggested that Aucubin induced the activation of Wnt/β-catenin signaling through promoting H19 expression. Conclusion. Our results demonstrated that Aucubin promoted osteogenesis in vitro and facilitated fracture healing in vivo through the H19-Wnt/β-catenin regulatory axis.